2014
DOI: 10.1074/jbc.m114.586495
|View full text |Cite
|
Sign up to set email alerts
|

The Merozoite Surface Protein 1 Complex Is a Platform for Binding to Human Erythrocytes by Plasmodium falciparum

Abstract: Background: Plasmodium falciparum invades red blood cells. Results: We show that the merozoite surface proteins MSPDBL1 and MSPDBL2 are part of the large MSP1 complex. Conclusion: The MSP1 complex acts as a platform for display of MSPDBL1 and MSPDBL2 on the merozoite surface. Significance: This provides important information on the structure of the merozoite surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 51 publications
2
55
1
1
Order By: Relevance
“…47 However, this study did not detect a direct interaction of MSP1 with human RBCs. In our view, this discrepancy could originate from the protein preparations used in that study.…”
contrasting
confidence: 71%
See 1 more Smart Citation
“…47 However, this study did not detect a direct interaction of MSP1 with human RBCs. In our view, this discrepancy could originate from the protein preparations used in that study.…”
contrasting
confidence: 71%
“…A full-length recombinant MSP1 assembled by tandem tethering of respective MSP1 fragments was used for the RBC binding assays. 47 Due to the poor solubility, recombinant full-length MSP1 was subjected to denaturation and renaturation steps, likely resulting in the loss of conformational folding and protein-binding activity. In our experience, recombinant MSP1 is best expressed as soluble subdomains without subjecting them to denaturation-renaturation steps (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…3D7, D10, K1, HB3, E8B, Palo Alto, and W2MEF strains were cultured as described previously (21). The D10PfMSP1-19 and D10PcMSP1-19 lines (where Pf is P. falciparum and Pc is Plasmodium chabaudi, respectively) were maintained with 24 ng/ml pyrimethamine (22), and 3D7⌬MSP3, 3D7⌬MSP6, and 3D7⌬MSPDBL1 lines were generated by transfection with constructs assembled in pCC1 (23). The PNG strain XHA_A has been reported previously (24), whereas all other PNG strains were adapted from erythrocytes cryopreserved in Glycerolyte 57 (Fenwal) from high-parasitemia baseline blood samples.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining ectodomain of MSP1 is shed into the bloodstream following invasion (8 -12). Other peripheral MSPs, such as MSP3, MSP6, MSP-DBL1, MSPDBL2, and MSP7, interact directly with MSP1 on the surface of parasites and are also shed following invasion (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…The peripheral proteins MSPDBL1 and MSPDBL2 bind to MSP1 on the parasite surface and facilitate binding to red blood cells (17)(18)(19). In a study utilizing peptide fragments for MSP3, synthetic MSP3 peptides were shown to have some involvement in binding to host erythrocytes (20).…”
mentioning
confidence: 99%